2014
DOI: 10.1007/s10753-014-9918-x
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin Inhibits Inflammation in Ischemia-Reperfusion Injury

Abstract: Ischemia/reperfusion (I/R) is associated with leukocyte accumulation and tissue injury. The aim of this research was to investigate the protective effect of simvastatin on hind limb I/R inflammation and tissue damage. Mice were subjected to hind limb ischemic insult for 2 h and were simultaneously administered an intraperitoneal injection of simvastatin (5 mg/kg); this was followed by 36 h of reperfusion. Myeloperoxidase (MPO) levels in the muscles of the hind limb were determined. CXC chemokines and pro-infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Proinflammatory mediators, such as TNF- α and IL-1 β , rapidly released from injured tissue in the initial phase of hind limb I/R are known to play a crucial role in hind limb I/R injury [30]. These cytokines could recruit inflammatory cells and regulate the permeability of blood and lymphatic vessels and lead to endothelial dysfunction [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Proinflammatory mediators, such as TNF- α and IL-1 β , rapidly released from injured tissue in the initial phase of hind limb I/R are known to play a crucial role in hind limb I/R injury [30]. These cytokines could recruit inflammatory cells and regulate the permeability of blood and lymphatic vessels and lead to endothelial dysfunction [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…This supported earlier work by Tong et al [ 32 ] who had found in amyloid precursor protein transgenic mice that Simvastatin attenuated inflammation, oxidative stress and reduced amyloid beta levels and the number of affected neurites. Simvastatin had also been shown to protect against tissue injury in the context of ischemia-reperfusion injury [ 33 ], and in a model of cardiopulmonary bypass to protect against cerebral and systemic inflammation, neuronal loss and memory impairment [ 34 ].…”
Section: Why Does Simvastatin Represent a Strong Candidate To Be A DImentioning
confidence: 99%
“…It has been reported that ischemic preconditioning [ 9 ], ischemic postconditioning [ 21 ], controlled reperfusion [ 22 ], hypothermia [ 23 ], light-emitting diode therapy [ 24 ] and some other physical therapies can relieve skeletal I/R injury [ 25 ]. In addition, several agents, such as dexamethasone [ 10 ], curcumin [ 26 ], salvianolic acid [ 8 ], silibinin [ 27 ], simvastatin [ 28 ], cyclosporine A [ 29 ], hydrogen-rich saline [ 30 ] and lipoxin A4 [ 4 ], have been shown to be effective in attenuating skeletal I/R injury. In cases of traumatic injuries in which I/R is not predictable and early intervention is desired, such strategies are not as relevant.…”
Section: Discussionmentioning
confidence: 99%